Calcineurin and Its Role in Synaptic Transmission - Tarasova, E. O.; Gaydukov, A. E.; Balezina, O. P. (Biochemistry (Moscow), 2018)
Calcineurin (CaN) is a serine/threonine phosphatase widely expressed in different cell types and structures including neurons and synapses. The most studied role of CaN is its involvement in the functioning of postsynaptic structures of central synapses. The role of CaN in the presynaptic structures of central and peripheral synapses is less understood, although it has generated a considerable interest and is a subject of a growing number of studies. The regulatory role of CaN in synaptic vesicle endocytosis in the synapse terminals is actively studied. In recent years, new targets of CaN have been identified and its role in the regulation of enzymes and neurotransmitter secretion in peripheral neuromuscular junctions has been revealed. CaN is the only phosphatase that requires calcium and calmodulin for activation. In this review, we present details of CaN molecular structure and give a detailed description of possible mechanisms of CaN activation involving calcium, enzymes, and endogenous and exogenous inhibitors. Known and newly discovered CaN targets at pre-and post-synaptic levels are described. CaN activity in synaptic structures is discussed in terms of functional involvement of this phosphatase in synaptic transmission and neurotransmitter release.